Peningkatan Keterampilan Motorik Halus Anak Melalui Metode Bermain Plastisin di RA Ar Rohmah - Susanti, Reni; Dewi, Resti Sulistia; Rosmina, Rosmina (EduSpirit : Jurnal Pendidikan Kolaboratif, 2024)
This study aims to analyze the effectiveness of the playdough-playing method in improving fine motor skills in children at RA Ar Rohmah. Fine motor skills are a crucial aspect of early childhood development, influencing daily activities such as writing, drawing, and buttoning clothes. The research employs a classroom action research (CAR) method consisting of several cycles, including planning, implementation, observation, and reflection. Data were collected through observations, interviews, and documentation, then analyzed descriptively. The results indicate a significant improvement in children’s fine motor skills after regularly engaging in playdough activities. Children participating in this activity showed enhanced hand-eye coordination, finger muscle strength, and creativity. Additionally, this method positively impacted children’s social and emotional aspects, increasing their interaction and self-confidence. This study recommends the widespread implementation of the playdough-playing method in early childhood education as an effective learning strategy.